Continuous production of carbon nanotubes and diamond films by swirled floating catalyst chemical vapour deposition method - A.S. Afolabi; A.S. Abdulkareem; S.E. Iyuke; H.C. van Zyl Pienaar (South African Journal of Science)
Various techniques for the synthesis of carbon nanotubes (CNTs) are being developed to meet an increasing demand as a result of their versatile applications. Swirled floating catalyst chemical vapour deposition (SFCCVD) is one of these techniques. This method was used to synthesise CNTs on a continuous basis using acetylene gas as a carbon source, ferrocene dissolved in xylene as a catalyst precursor, and both hydrogen and argon as carrier gases. Transmission electron microscopy analyses revealed that a mixture of single and multi-wall carbon nanotubes and other carbon nanomaterials were produced within the pyrolytic temperature range of 900 - 1 100Â°C and acetylene flow rate range of 118 - 370 ml min - 1. Image comparison of raw and purified products showed that low contents of iron particles and amorphous carbon were contained in the synthesised carbon nanotubes. Diamond films were produced at high ferrocene concentration, hydrogen flow rate and pyrolysis temperatures, while carbon nanoballs were formed and attached to the surface of theCNTs at low ferrocene content and low pyrolysis temperature.